IMPLEMENTATION OF THE SYSTEM MATHEMATICA INTO EDUCATION OF ECONOMISTS AND MANAGERS - MOSOVA, Vratislava (Trends in education, 2010)
The possibility to implement the mathematical software into education of economists and managers is discussed in the article. The advantages of the utilization of the system Mathematica are demonstrated via examples of loan repayments and simulation of market behavior.
Keywords: software Mathematica; amortization; model of market.